Likovna kritika u povodu Hrvatskog salona - Galjer, Jasna (Array, 1998)
The Society of Artists put on view in 1898, in the newly opened Art Pavilion, a programmatic exbition entitled, in the fin-de-siecle spirit, Croatian Salon and accompanied by a publication of the same title containing notes on artists, poetry and prose, and programmatic texts by M.Dežman and Ksaver Šandor Gjalski. Soon there appeared critical interpretations of the Salon by I. Kršnjavi, Franjo Š. Kuhač, Franjo Marković and Ante Tresić Pavičić. Importatnt is also the interpretation of Petar Skok (1900) and Josip Bogner(1930).